Perkawinan Campuran Perspektif Undang-Undang Perkawinan di Indonesia - Sunanta, Sunanta (El 'Ailaah, 2025)
This study aims to find out how mixed marriage is in the review of the Marriage Law in Indonesia. This study uses a type of library study that is qualitative. The results of this study show that mixed marriage is generally the same as the implementation of ordinary (non-mixed) marriage. The stages are also the same as the marriage recorded in the KUA and special requirements for parties of different nationalities, including the permission of the embassy of the other race's home country, which makes it clear that there are no obstacles in marriage. Marriage registration is important in mixed marriages, not only as an administrative order but also as a legally binding and appropriate force.